High-Density Electromyography Provides Improved Understanding of Muscle Function for Those With Amputation - Kuruganti, Usha; Pradhan, Ashirbad; Toner, Jacqueline (Frontiers in Medical Technology, 2021)
Surface electromyography (EMG) has been used successfully as a control input for powered prostheses. The ability to harness information from this biological signal has helped to advance prosthesis design greatly over the last several decades. These signals provide insight into muscle properties however have been limited due to the nature of the signal and single electrode site. Over the last decade, researchers have made significant advances using multiple electrode sites also known as high-density surface EMG (HDsEMG) to gather more information from the muscle and overcome previous limitations. This technique is promising for not only the development of myoelectric-controlled prostheses but also advancing our knowledge of muscle behaviour with clinical populations, including post amputation. Furthermore, information from the HDsEMG signal can be used to estimate muscle properties of both the residual limb and the intact limb. Spatial features of the HDsEMG signal have been used to better understand upper limb prostheses, however, the use of this technology to examine amputated lower limbs, particularly in movements outside of gait, has been less prevalent To our knowledge, there have been no studies using HDsEMG and spatial information during isokinetic movements. In this study HDsEMG was used to examine the rectus femoris muscle in both able-bodied individuals and one individual with a lower limb amputation during isokinetic knee extension. Spatial features of the HDsEMG signal are compared over a range of speeds. In addition, a new trajectory-based method of examining the centroid of the HDsEMG activation map is presented. The advent of new non-invasive biological signal acquisition systems, as well as advanced signal processing techniques, will enable researchers to advance fundamental understanding of neuromuscular function in clinical populations.